EXPERTS 1—experiences of long-term life-limiting conditions among patients and carers: protocol for a qualitative meta-synthesis and conceptual modelling study. Issue 4 (2nd April 2015) - May, Carl R; Masters, Jayne; Welch, Lindsay; Hunt, Katherine; Pope, Catherine; Myall, Michelle; Griffiths, Peter; Roderick, Paul; Glanville, Julie; Richardson, Alison
Abstract : Introduction: Increasing numbers of the population are living with long-term life-limiting conditions with a significant proportion characterised by multimorbidity. Patients with these conditions often experience high volumes of clinical interaction involving them, their caregivers and healthcare providers in complex patterns of organising, coordinating, negotiating and managing care. A better understanding of the sources of experienced complexity and multimorbidity, from the patient perspective is paramount to improve capacity and manage workload to promote improved experience of illness, more effective healthcare utilisation and improved healthcare outcomes. To better understand the sources of complexity we will undertake an evidence synthesis of qualitative studies of patient and informal carer experiences of three common long-term life-limiting conditions. We will investigate what is known about these diseases at different stages in disease progression, treatment regimens and places of care. Method and analysis: We will include qualitative studies of patients' and carers' (aged >18) accounts of their experiences of healthcare provision in a range of settings and healthcare systems. We will conduct an extensive electronic database search of publications in English between 2000 and 2014. Results and discussions sections of the papers will be regarded as formal data using the constant comparison method of qualitative analysis. From the meta-synthesis results, we will build a conceptual model of mechanisms and processes that shape patients' journeys towards end of life to suggest where in the patient journey new interventions to improve patient and carer experience can be developed and delivered. The study is being conducted between 1 December 2014 and 31 December 2015. Ethics and dissemination: No human subjects or personal data are involved and no ethical issues are anticipated. An important element of dissemination is informing user communities about the practical implications of the work through workshops, meetings and social media. Scientific results will be published in peer reviewed journals and disseminated through conferences. Trial registration number: PROSPERO CRD42014014547.